Pertimbangan Hukum Mahkamah Agung Memutus Perkara Penipuan Secara Berlanjut dan Pencucian Uang - Achmad Mirza Fahlevi (Verstek, 2019)
This study aims to determine the consideration of the Supreme Court adjudicating the Cassation appeal to the case of continuous fraud and money laundering. The research method used is normative legal research. The approach used is the approach of law and case approach. Sources of legal materials used are primary and secondary legal materials. It is known that the Supreme Court’s consideration granted the Cassation appeal to the case of continuous fraud and money laundering with Defendant Masjaya bin Nurdin proven legally and convincingly guilty of committing a criminal act “Continuous Fraud and Money Laundering” and imposing a penalty on the Defendant therefore by criminal imprisonment for 8 (eight) years and a fne of Rp. 1,000,000,000 (one billion rupiah), provided that if the fne is not paid, the Defendant shall be subject to a fve-month imprisonment based on the error of judex facti considering the element of deceit or lies from the actions of the Defendant, CV business. GDC from Makassar RegionalGovernment is to trade herbal medicine, but in fact CV. GDC does not do herbal medicine, but collects funds from the community. therefore, the balance of the Supreme Court is in conformity with the provisions contained in Article 256 jo of Article 193 paragraph (1) of the Criminal Procedure Code. Keywords: Judge Consideration, Money Laundering Crime, Crime Fraud.